Social connectedness and dementia prevention: Pilot of the APPLE-Tree video-call intervention during the Covid-19 pandemic. (November 2021) - Cooper, Claudia; Mansour, Hassan; Carter, Christine; Rapaport, Penny; Morgan-Trimmer, Sarah; Marchant, Natalie L; Poppe, Michaela; Higgs, Paul; Brierley, Janine; Solomon, Noa; Budgett, Jessica; Bird, Megan; et al.
Background and Objectives: The Covid-19 pandemic reduced access to social activities and routine health care that are central to dementia prevention. We developed a group-based, video-call, cognitive well-being intervention; and investigated its acceptability and feasibility; exploring through participants' accounts how the intervention was experienced and used in the pandemic context. Research Design and Method: We recruited adults aged 60+ years with memory concerns (without dementia). Participants completed baseline assessments and qualitative interviews/focus groups before and after the 10-week intervention. Qualitative interview data and facilitator notes were integrated in a thematic analysis. Results: 12/17 participants approached completed baseline assessments, attended 100/120 (83.3%) intervention sessions and met 140/170 (82.4%) of goals set. Most had not used video calling before. In the thematic analysis, our overarching theme was social connectedness . Three sub-themes were as follows:Retaining independence and social connectedness : social connectedness could not be at the expense of independence;Adapting social connectedness in the pandemic : participants strived to compensate for previous social connectedness as the pandemic reduced support networks;Managing social connections within and through the intervention: although there were tensions, for example, between sharing of achievements feeling supportive and competitive, participants engaged with various lifestyle changes; social connections supported group attendance and implementation of lifestyle changes. Discussion and Implications: Our intervention was acceptable and feasible to deliver by group video-call. We argue that dementia prevention is both an individual and societal concern. For more vulnerable populations, messages that lifestyle change can help memory should be communicated alongside supportive, relational approaches to enabling lifestyle changes.